Contribution to the Tb-doped AlNxOy:H/c-Si(p) interface study using Surface Photovoltage (SPV) techniques for potential photovoltaic applications - Dulanto Carbajal, Jorge Alejandro (2023)
Hydrogenated Aluminum Oxynitride (AlNxOy:H) is a versatile material for the surface passivation of crystalline silicon (c-Si). The capability of having positive or negative fixed charges makes AlNxOy:H a suitable material for surface passivation of both n-type and p-type c-Si. Terbium (Tb) implemented in thin films is known for its potential for downshifting light. This work studies the electronic properties of the Tb-doped AlNxOy:H/cSi(p) interface. The studied samples’ layers were deposited by reactive direct current (DC) sputtering with different hydrogen flows and then annealed. Due to high leakage currents and high defect densities, the electronic properties of the Tb-doped AlNxOy:H layers could not be analyzed conclusively using standard techniques such as high-frequency capacitance-voltage (HF-CV) or quasi-steady-state photoconductance (QSSPC) measurements, respectively. As an alternative, the non-contact Surface Photovoltage (SPV) characterization technique enabled a profound investigation of the electronic features of the Tb-doped AlNxOy:H/c-Si (p) interface. Both modulated SPV and transient SPV measurements are performed. The capabilities of the SPV measurements make this technique unique and very effective in observing and measuring critical passivation properties of the Tb-doped AlNxOy:H samples. Particularly the transient SPV of the Tb-doped AlNxOy:H samples enabled the observation of different optical transitions (band to band, band to defect, defect to band) and carrier transport mechanisms between the Si surface and the Tb-doped AlNxOy:H. The changes in relaxation times among Tb-doped AlNxOy:H samples are noticeable due to spatial separation among defects (tunneling). This study uses complementary measurements like X-ray reflectometry (XRR), Photoluminescence (PL) and Fourier-transform infrared spectroscopy (FTIR) to obtain valuable information about the AlNxOy:H layer and the AlNxOy:H/c-Si(p) interface that validates the SPV results and observations. In the c-Si, through SPV, we observed strong accumulation with passivation of boron acceptors and the generation of defects near the interface. When the hydrogen flow was increased, the net negative charge in the Tbdoped AlNxOy:H layer decreased, and the surface photovoltage signals associated with defects increased. Transients SPV at higher hydrogen flows decayed faster, and hopping transport via an exponential distribution of trap states in energy replaced trap-limited relaxation of charge carriers separated in space. The particular conditions that these AlNxOy:H samples have, make transient SPV spectroscopy a unique and reliable technique to observe the electronic properties of the AlNxOy:H/c-Si(p) interface.